2013
DOI: 10.12928/kesmas.v6i3.1053
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kinerja Perawat Dalam Pengendalian Infeksi Nosokomial Di Rsu Pku Muhammadiyah Bantul Yogyakarta

Abstract: Background: Nosocomial infection is an important health care problem worldwide. Nosocomial infections in the hospital at about 9% (variation 3-21%) or over 1.4 million patients admitted to hospitals around the world. Nosocomial infections pose some problems, namely an increase in morbidity and mortality, the addition of day care, the increasing cost of care and dissatisfaction with both patients and their families. Nosocomial infection control efforts are very complex and involves a variety of targets includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
1
4
0
2
Order By: Relevance
“…The use of PPE is not affected by the level of education there. This is because the average respondent has a Diploma in education.This is in accordance with previous research conducted by Herpan 2012 where the results of the research obtained a p-value = 0.486 which means that the relationship between education and nurse performance in controlling INOS at PKU Bantul Hospital Yogyakarta is not significant, or there is no relationship between education and nurse performance in controlling INOS at PKU Bantul Hospital Yogyakarta (Herpan, 2012).The higher the level of education, the more likely the workforce can work and carry out their work.…”
Section: The Relationship Between the Level Of Nursing Education And ...supporting
confidence: 90%
“…The use of PPE is not affected by the level of education there. This is because the average respondent has a Diploma in education.This is in accordance with previous research conducted by Herpan 2012 where the results of the research obtained a p-value = 0.486 which means that the relationship between education and nurse performance in controlling INOS at PKU Bantul Hospital Yogyakarta is not significant, or there is no relationship between education and nurse performance in controlling INOS at PKU Bantul Hospital Yogyakarta (Herpan, 2012).The higher the level of education, the more likely the workforce can work and carry out their work.…”
Section: The Relationship Between the Level Of Nursing Education And ...supporting
confidence: 90%
“…This study was in line with the exploration conducted by Yuniar in 2013, which stated that there was a significant relationship between knowledge and nurse performance in preventing nosocomial infections at PKU Bantul Hospital, Yogjakarta, with a p-value of 0.000. That respondents with low knowledge had the opportunity not to control INOS 7.115 times (Herpan and Wardani, 2013). Acceptance of behavior change in a person can be assessed through the level of a person's knowledge, attitudes, and practices to achieve health authority.…”
Section: Discussionmentioning
confidence: 99%
“…The level of knowledge, good preparedness, age level, and the absence of misunderstandings in providing information are included in predisposing factors in risk management to anticipate COVID-19 (Shi et al, 2020). This makes health workers better prepared to prevent COVID-19 in the workplace (Herpan and Wardani, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study showed that there is a relationship between education level and nurses' performance in preventing healthcare associated infections. Education is the act or process that planned to affect others, either individually, groups, or communities so that they will do as the lecturer expected [7]. As in [8], education will affect a person in making decisions so that the higher the education level, the more understand the person about knowledge and will affect their behaviors, so their compliance behavior also will be higher.…”
Section: Discussionmentioning
confidence: 99%